"IDEALOGY AND TRANSLATION IMPACTS" - Khadija Khaldarova (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Ideology in translation has been the subject of many researches done by different scholars, since it is very challenging and troublesome in the process of translation. It does not have a specific meaning, and it can be defined in various ways by common people, scholars, experts, and many others.Ideology is animportant factor which can affect translation process and the final product available to its audience.In political contexts, considering ideology and using it while translating has the potential to lead to mistranslation and it can show the power relations from a particular point of view. In this paper thetranslation ofJoint Plan of Action, an agreement between Islamic Republic of Iran and E3+3,has been analyzed through CDA model to find the impacts of ideology on.